2014
DOI: 10.1039/c4ra10271a
|View full text |Cite
|
Sign up to set email alerts
|

A coarse-grained molecular dynamics – reactive Monte Carlo approach to simulate hyperbranched polycondensation

Abstract: A coarse-grained molecular dynamics (CG-MD) and reactive Monte Carlo (RMC) hybrid method (CG-MD + RMC) has been developed to investigate the hyperbranched polycondensation of 3,5-bis(trimethylsiloxy) benzoyl chloride to poly(3,5-dihydroxybenzoic acid). The CG force field to describe the formation of the hyperbranched macromolecules has been extracted from all-atom molecular dynamics simulations by the mapping technology of iterative Boltzmann inversion. In the mapping process branched poly(3,5-dihydroxybenzoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 97 publications
0
19
0
1
Order By: Relevance
“…Genzer et al, [4,5] He and the coworkers, [6,7] Berezkin et al, [8][9][10][11] Lu et al, [12] Yong et al, [13,14] Jang, [15] and Mukherji et al, [16] including Rabbel et al [17] in their recent works, all adopted similar reaction probability-based protocols to establish their respective reaction models. The simulation studies based on this idea can be identified as the second class, that is, "probability-based" protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Genzer et al, [4,5] He and the coworkers, [6,7] Berezkin et al, [8][9][10][11] Lu et al, [12] Yong et al, [13,14] Jang, [15] and Mukherji et al, [16] including Rabbel et al [17] in their recent works, all adopted similar reaction probability-based protocols to establish their respective reaction models. The simulation studies based on this idea can be identified as the second class, that is, "probability-based" protocols.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter cA represents the conversion of A functional group and is calculated as the ratio of the number of reacted A groups to the initial number. Differently from the previous work, cA will dynamically change with polymerization progress.…”
Section: Methods and Algorithmmentioning
confidence: 81%
“…They found that the diffusion of reactants greatly influences the constructed network structure. Zhang and He, by combining the reactive Monte Carlo method with the coarse‐grained molecular dynamics, showed a very good agreement of AB 2 system between the experimental results and the simulation. But the drawback of their work is that the efficiency is quite low due to the lack of parallelization in the implementation of their algorithm.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Apart from using fine‐scale atomistic force‐fields, coarse‐grained force fields (CGFF) are recently used to build polymer systems . There are multiple major advantages of modeling polymer networks at a coarse‐grained level, compared to the atomistic level.…”
Section: Introductionmentioning
confidence: 99%